Pemberdayaan Masyarakat Pesisir melalui Transplantasi Karang untuk Mendukung Pariwisata Berkelanjutan di Taman Laut Pandanan Kabupaten Lombok Utara - Bratayasa, I Wayan; Idrus, Syech; Martayadi, Uwi; Prayuda, Danu Satria; Subadra, I Nengah (LOSARI DIGITAL, 2026)
This community service activity aims to integrate coral reef restoration with the socio-economic empowerment of coastal communities. The method employed is a participatory, learning-by-doing approach, in which the community is directly involved in all stages, ranging from the production of transplant media to monitoring. The techniques applied include the use of sandy substrates in resin–catalyst layering to enhance coral attachment, as well as planting at depths of 10–15 meters, adjusted to ecological conditions. The results of the activity indicate an improvement in the technical capacity of the community and the emergence of new business opportunities, such as the production of spider frames and conservation-based educational tourism. This program demonstrates that coral transplantation can serve as an effective strategy for ecosystem rehabilitation while simultaneously supporting the development of sustainable marine ecotourism.